The eleventh plague - Hirsch, Jeff. (New York : Scholastic Press, 2011)
Twenty years after the start of the war that caused the Collapse, fifteen-year-old Stephen, his father, and grandfather travel post-Collapse America scavenging, but when his grandfather dies and his father decides to risk everything to save the lives of two strangers, Stephen's life is turned upside down.
Accelerated Reader AR
Keywords: Survival -- Juvenile fiction; Regression (Civilization) -- Juvenile fiction; Grandfathers -- Death -- Juvenile fiction; Death -- Juvenile fiction; Adolescence -- Juvenile fiction; Plague -- Juvenile fiction; Young adult fiction; Science fiction; Robinsonades; Dystopias